Synthesis, characterization, and monoamine transporter activity of the new psychoactive substance 3′, 4′‐methylenedioxy‐4‐methylaminorex (MDMAR). Issue 7 (20th October 2014) - McLaughlin, Gavin; Morris, Noreen; Kavanagh, Pierce V.; Power, John D.; Twamley, Brendan; O'Brien, John; Talbot, Brian; Dowling, Geraldine; Mahony, Olivia; Brandt, Simon D.; Patrick, Julian; Archer, Roland P.; et al.
<x xml:space="preserve">Abstract</x> The recent occurrence of deaths associated with the psychostimulant cis‐4, 4′‐dimethylaminorex (4, 4′‐DMAR) in Europe indicated the presence of a newly emerged psychoactive substance on the market. Subsequently, the existence of 3, 4‐methylenedioxy‐4‐methylaminorex (MDMAR) has come to the authors' attention and this study describes the synthesis of cis‐ and trans‐MDMAR followed by extensive characterization by chromatographic, spectroscopic, mass spectrometric platforms and crystal structure analysis. MDMAR obtained from an online vendor was subsequently identified as predominantly the cis‐isomer (90%). Exposure of the cis‐isomer to the mobile phase conditions (acetonitrile/water 1:1 with 0.1% formic acid) employed for high performance liquid chromatography analysis showed an artificially induced conversion to the trans‐isomer, which was not observed when characterized by gas chromatography. Monoamine release activities of both MDMAR isomers were compared with the non‐selective monoamine releasing agent (+)‐3, 4‐methylenedioxymethamphetamine (MDMA) as a standard reference compound. For additional comparison, both cis‐ and trans‐4, 4′‐DMAR, were assessed under identical conditions. cis‐MDMAR, trans‐MDMAR, cis‐4, 4′‐DMAR and trans‐4, 4′‐DMAR were more potent than MDMA in their ability to function as efficacious substrate‐type releasers at the dopamine (DAT) and norepinephrine (NET) transporters in rat brain tissue. While cis‐4, 4′‐DMAR, cis‐MDMAR and trans‐MDMAR were fully efficacious releasing agents at the serotonin transporter (SERT), trans‐4, 4′‐DMAR acted as a fully efficacious uptake blocker. Currently, little information is available about the presence of MDMAR on the market but the high potency of ring‐substituted methylaminorex analogues at all three monoamine transporters investigated here might be relevant when assessing the potential for serious side‐effects after high dose exposure. Copyright © 2014 John Wiley & Sons, Ltd.